1994
DOI: 10.1177/104438949407500504
|View full text |Cite
|
Sign up to set email alerts
|

Coping and Adaptation Patterns among Chinese, Indian, and Malay Families Caring for a Mentally Ill Relative

Abstract: Families caring for chronically mentally ill relatives often experience considerable stress and hardship. To adapt, family members must learn new coping strategies and make sufficient use of informal and formal support systems in the community. The authors examined cultural variations in the coping and adaptation process among three main ethnic groups in Singapore (Chinese, Malay, and Indian). Interviews conducted with primary caregivers in 30 families showed cross-cultural differences in the adverse effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
2
12
1
Order By: Relevance
“…The participants reported that they drew both physical resources and psychological support from their families. This confirms the literature on family studies stating that in times of crisis, the family, as a functioning unit, also goes through the stress-and-coping process (Bentelspacher et al, 1994;McCubbin & Patterson, 1982;Patterson, 1998Patterson, , 2002. However, some families fare better than others do.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The participants reported that they drew both physical resources and psychological support from their families. This confirms the literature on family studies stating that in times of crisis, the family, as a functioning unit, also goes through the stress-and-coping process (Bentelspacher et al, 1994;McCubbin & Patterson, 1982;Patterson, 1998Patterson, , 2002. However, some families fare better than others do.…”
Section: Discussionsupporting
confidence: 72%
“…From their reports, a pattern of Singaporeans coping with uncontrollable traumas and natural disasters emerged; that is, they coped as families and not as isolated individuals, and the family functioned as a unit of response. This led us to the hypothesis that in this collectivistic Asian country (Hofstede, 1980), where people come from a long history of having family-oriented cultures (Bentelspacher, Chitran, & Rahman, 1994), individuals, when faced with major life threats, cope in a collectivistic way, whereby the family functions as a team or an integrated unit in the stress-and-coping process. The construct of family resilience (Walsh, 1998a(Walsh, , 2003Patterson, 2002) was introduced as a family characteristic that enables families to withstand and rebound from the disruptive challenges they face.…”
Section: Introductionmentioning
confidence: 99%
“…As the above quotes indicate, for many non‐Chinese informants, migrant Chinese values were often sharply contrasted with the apparent and much lauded ‘tolerance’ of Dayak (indigenous inhabitants of Borneo) and Malay families, this being a commonly held assumption in the hospital, supported to some extent in other research studies of Chinese, Malay and Indian families (Bentelspacher et al . 1994, pp.…”
Section: Resultsmentioning
confidence: 63%
“…Higher subjective levels of burden and personal stress have been reported by high EE relatives compared with low EE relatives 19. For many carers, frustration, anger, loneliness and despair are common 20–22. Levene et al 3 reported that the Perceived Family Burden Scale, an instrument for measuring patient behaviour and family burden, demonstrated predictive power for early symptomatic relapse in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%